Pemanfaatan Aplikasi Powton untuk Pelatihan Presentasi dan Video pada PT. Jaya Persada Indonesia (JPI) - Sanwani; Eko Setia Budi; Eva Zuraidah; Ade Priyatna; Siti Indriane Maebari; Yoki Feriano; Alfin Nugraha; Yeni Nuraeni; Mohammad Aswad Arifin (Akademi Farmasi YPPM Mandiri, 2022)
PT. Jaya Persada Indonesia or JPI is a company founded with the spirit of togetherness. Seeing its opportunities for the development of property and human resources, the company is currently focusing on the business area carried out by PT. Jaya Persada Indonesia in the field of Property Developer, Property Agency (JPI Propertindo). Limited understanding of the Powton Application used for presentations and making videos is the reason Nusa Mandiri University carried out Community Service in the form of Utilizing the Powton Application for presentation training and making videos at PT. Jaya Persada Indonesia (PT. JPI) in East Jakarta. With this training, it can help staff and management in making interesting presentations and videos within PT. Jaya Persada Indonesia (PT. JPI).